2008
DOI: 10.2174/187221008783478626
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured p-Type Semiconducting Transparent Oxides: Promising Materials for Nano-Active Devices and the Emerging Field of “Transparent Nanoelectronics”

Abstract: Transparent conducting oxides (TCO) with p-type semiconductivity have recently gained renewed interest for the fabrication of all-oxide transparent junctions, having potential applications in the emerging field of 'Transparent' or 'Invisible Electronics'. This kind of transparent junctions can be used as a "functional" window, which will transmit visible portion of solar radiation, but generates electricity by the absorption of the UV part. Therefore, these devices can be used as UV shield as well as UV cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 208 publications
(195 reference statements)
0
3
0
Order By: Relevance
“…But most importantly, it can be doped into a p-type TSO with divalent or tri-valent cations (Cr, Fe, Ni, Co, etc.). The p-type TSOs are extremely important in the field of emerging transparent electronics for the potential fabrication of invisible circuits [69] for UV-based solar cells [351,352]. Hence, considerable attention was given to the syntheses and doping strategies to fabricate p-type TiO 2 as TSOs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But most importantly, it can be doped into a p-type TSO with divalent or tri-valent cations (Cr, Fe, Ni, Co, etc.). The p-type TSOs are extremely important in the field of emerging transparent electronics for the potential fabrication of invisible circuits [69] for UV-based solar cells [351,352]. Hence, considerable attention was given to the syntheses and doping strategies to fabricate p-type TiO 2 as TSOs.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for a highly sensitive, selective, and stable hydrogen sensor has increased in recent years mainly due to the continued and growing importance of hydrogen in fuel cell applications [329], as well as the chemical, semiconductor, food processing, and petroleum industries. Various types of sensor technologies are being developed [330], such as Schottky junctions [331][332][333][334], fiber optics [335][336][337][338][339], catalysis [338][339][340], electrochemical techniques [341][342][343][344], field-effect transistors (FETs) [345][346][347], oxide semiconductors [72,325,[348][349][350][351][352], and combinations of these. Gasochromic TiO 2 devices have been gaining importance in recent years due to a large number of applications, such as gas sensing, smart windows, and display industries [353,354].…”
Section: Other Energy-related Applicationsmentioning
confidence: 99%
“…Raman scattering measurements on CuAlO 2 and CuGaO 2 have reported that these compounds transform to unresolved structures above 34 and 26 GPa, respectively [168][169]. X-ray diffraction, Mossbauer and XAS measurements on CuFeO 2 reveal intricate structural/electronic-magnetic pressure induced phase transition [170][171].…”
Section: Structural Changesmentioning
confidence: 99%